Seeking the sun in deep, dark places: mesopelagic sightings of ocean sunfishes (Molidae). Issue 4 (16th September 2015) - Phillips, N. D.; Harrod, C.; Gates, A. R.; Thys, T. M.; Houghton, J. D. R.
<x xml:space="preserve">Abstract</x> Evidence is presented from publicly available remotely operated vehicle (ROV) footage that suggests deep‐water ranging in ocean sunfishes (family Molidae) is more common than typically thought, including a new maximum depth recorded for the southern sunfish Mola ramsayi.